High-strength and high-conductivity AuNiCu alloy and preparation method thereof
The method of forming a nanotwin structure through low-temperature cold rolling treatment of liquid nitrogen solves the problem of negatively related to the conductivity of gold-based alloys in traditional processes, and achieves the balance of high strength and high conductivity of AuNiCu alloys.
Patent Information
- Application Number
- CN202510082471.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
While improving the strength of the gold-based alloy, traditional preparation processes will reduce the conductivity of the alloy, resulting in a negative correlation between strength and conductivity, making it difficult to take into account both high strength and high conductivity.
The liquid nitrogen low-temperature cold rolling treatment method is used to melt, cast and anneale the raw materials of AuNiCu alloy, and then the low-temperature cold rolling treatment is carried out at the liquid nitrogen temperature, and the cold rolling pressure is controlled to be 15%-30% to form a nanotwin structure.
The nanotwin structure formed by low-temperature cold rolling treatment of liquid nitrogen improves the tensile strength of AuNiCu alloy to 372-585MPa, and enhances the conductivity of 11.8%-27.5% IACS, achieving both high strength and high conductivity.
Smart Images

Figure BDA0005249094480000041 
Figure BDA0005249094480000045
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gold-based electrical contact material preparation, and specifically relates to a high-strength and high-conductivity AuNiCu alloy and a preparation method thereof. Background Art
[0002] Gold-copper-nickel alloy has excellent chemical stability, significant electrical contact properties, and a low yield point and elastic modulus. These properties ensure the contact stability of the alloy material, enabling the alloy to work stably under special environments, making it an ideal electrical contact material under conditions of low contact pressure and weak current. Therefore, it has broad application prospects in the fields of electrical contact materials, aerospace, and military precision instruments.
[0003] However, with the rapid development of science and technology, various fields have put forward higher requirements on the strength, conductivity, and service life of electrical contact materials. The traditional preparation process will reduce the conductivity of the alloy while improving the strength of the gold-based alloy. There is a negative correlation between the strength of the gold-based alloy and its conductivity. Therefore, how to improve the strength of the gold-based electrical contact material while maintaining good conductivity is a key issue that needs to be solved urgently.
[0004] In view of the problem that there is an inverted relationship between the strength and electrical conductivity of gold-based alloys, the present invention adopts a liquid nitrogen low-temperature cold rolling treatment method, melts, casts and anneals AuNiCu alloy raw materials to obtain alloy sheet blanks, performs low-temperature cold rolling treatment on the alloy sheet within the temperature range of liquid nitrogen, controls the cold rolling reduction, increases the dislocation density and local stress, drives the nucleation and growth of nanotwins, and forms more nanotwins, thereby preparing an AuNiCu alloy material with both high strength and high electrical conductivity. Summary of the invention
[0005] In order to solve the problems existing in the technical background, the purpose of the present invention is to provide a high-strength and high-conductivity AuNiCu alloy. The AuNiCu alloy material is subjected to liquid nitrogen low-temperature cold rolling treatment to form nanotwins with a lamellar structure, and the volume content of the nanotwins is between 7.3% and 32.8%, and finally an AuNiCu alloy with a strength of 372-585MPa and a conductivity of 11.8%-27.5% IACS is obtained.
[0006] Another object of the present invention is to provide a method for preparing the high-strength and high-conductivity AuNiCu alloy, by cooling the AuNiCu alloy to liquid nitrogen temperature and performing low-temperature cold rolling treatment to promote the formation of nano twins with a lamellar structure, and the nano twin boundaries can hinder the movement of dislocations and reduce the scattering of electrons, thereby effectively improving the strength and conductivity of the alloy. The specific process is: first, the AuNiCu alloy sheet obtained by pretreatment is immersed in liquid nitrogen (immersion time is 0.5h~1.5h, cooling temperature is -196°C), so that it is cooled to liquid nitrogen temperature, and then the alloy sheet is quickly taken out from the liquid nitrogen and placed in a rolling mill, and the AuNiCu alloy is cold rolled with a reduction of 15%-30% in a low temperature (-196°C) environment of liquid nitrogen; after each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling to ensure that it is always in a low temperature state of -196°C.
[0007] Preferably, the AuNiCu alloy of the present invention contains 91% Au, 7.5% Ni and 1.5% Cu.
[0008] Preferably, the pretreatment of the AuNiCu alloy sheet of the present invention is specifically as follows:
[0009] (1) Melting: placing the alloy raw material in a vacuum tube furnace for melting at a melting temperature of 1050-1250° C.;
[0010] (2) Casting: Casting the obtained alloy into AuNiCu alloy sheet through casting and cooling process;
[0011] (3) Annealing: The obtained alloy sheet is placed in a tube furnace and heated to 500-700°C, kept at this temperature for 1-2 hours, and then naturally cooled to room temperature;
[0012] (4) Cleaning and drying: Use anhydrous ethanol to clean the surface of the alloy sheet and place it in a vacuum drying oven to dry.
[0013] The AuNiCu alloy material obtained by the liquid nitrogen low-temperature cold rolling process of the present invention has both high strength and high conductivity, and can meet the basic requirements in the technical fields of precious metal-based electrical contacts and the like.
[0014] The present invention soaks the AuNiCu alloy sheet blank obtained by pretreatment in liquid nitrogen, cools it to the liquid nitrogen temperature and performs low-temperature cold rolling treatment, and finally obtains a high-strength and high-conductivity AuNiCu alloy by controlling the reduction amount to be 15%-30%, wherein the tensile strength is 372-585MPa and the conductivity is 11.8%-27.5%IACS; on the one hand, when the AuNiCu alloy is subjected to low-temperature cold rolling treatment at the liquid nitrogen temperature, compared with the room temperature, the atomic migration rate is reduced, the dislocation movement is hindered, and the slip becomes more difficult; on the other hand, as the cold rolling deformation increases, the local stress is enhanced, which promotes the twinning deformation of the grains and then forms nano twins; for the nano twins, the nano twin boundary hinders the movement of the dislocation, and the external stress required for the dislocation to pass through the nano twin boundary increases, thereby improving the overall mechanical properties of the alloy. In addition, the electron scattering coefficient of the nanotwin boundary is one order of magnitude lower than that of the ordinary grain boundary, and the electron scattering effect is smaller, thereby enhancing the conductivity of the alloy; therefore, the nanotwins formed by liquid nitrogen low-temperature cold rolling treatment play a key performance enhancement role in the preparation of high-strength and high-conductivity AuNiCu alloys.
[0015] Principle of the Invention
[0016] 1. Principle of promoting the formation of AuNiCu alloy nanotwins by liquid nitrogen low temperature cold rolling treatment
[0017] For most body-centered cubic metals, the internal structure is less symmetrical and the atomic arrangement is relatively tight, so it is difficult to form nano twins during processing; while face-centered cubic metals are relatively easy, such as common metals such as Al, Cu, Au, Ni, Ag, etc. These materials generally need to be able to form nano twins under low-temperature processing conditions. Compared with room temperature, the low-temperature environment can limit dislocation slip, induce twin deformation of grains, and promote the formation of nano twins. The AuNiCu alloy in the present invention forms nano twins with a lamellar structure after a certain amount of liquid nitrogen low-temperature cold rolling. During the experiment, it was found that the formation of AuNiCu alloy nano twins has a certain correlation with the processing deformation amount. Too small deformation will lead to insufficient local stress, which is difficult to promote twin deformation of the internal grains of AuNiCu alloy. The present invention carried out 5% and 10% liquid nitrogen low-temperature cold rolling of AuNiCu alloy before conducting the experiment of the following embodiment, but due to too little reduction, the formation of nano twins was basically not observed, and it is also possible that the content of nano twins formed is too little to be accurately detected. In conclusion, too small a processing deformation is not conducive to the twinning deformation of the internal grains of the AuNiCu alloy, and has a certain influence on the formation of nanotwins. In addition, the formation of nanotwins is also related to the stacking fault energy of the AuNiCu alloy. High stacking fault energy tends to promote dislocation slip, while low stacking fault energy is conducive to the formation of nanotwins. The stacking fault energy of Cu is relatively low, and the stacking fault energy of Au is smaller than that of Cu. Moreover, the stacking fault energy of the alloy decreases with the increase of low stacking fault energy elements, so the stacking fault energy of the AuNiCu alloy is lower than that of Cu. Moreover, the stacking fault energy of the alloy is positively correlated with temperature. Low temperature environment can reduce the stacking fault energy of the alloy. Therefore, liquid nitrogen low-temperature cold rolling treatment is more conducive to inducing twinning deformation of the internal grains of the AuNiCu alloy and promoting the formation of nanotwins.
[0018] According to the Hall-Page law and combined with experimental data, the relationship between the content of nanotwins formed by liquid nitrogen low-temperature cold rolling and the cold rolling reduction is obtained as follows:
[0019]
[0020] in, is the nanotwin content of the alloy after cold rolling, ξ is the cold rolling reduction, B, C and K are constants obtained by fitting the experimental data;
[0021] Substituting the experimental data into the relationship between the nano twin content and the cold rolling reduction is:
[0022] (ξ takes 15%-30%)
[0023] When the cold rolling reduction is 15%-30%, the content of the formed nano twins is 7.3%-32.8%.
[0024] In terms of mechanical properties, according to the Hollomon model, the relationship between the nanotwin content and the tensile strength of the alloy is:
[0025]
[0026] Among them, σ is the tensile strength of the alloy after cold rolling, σ0 is the initial tensile strength of the alloy (σ0 = 317MPa), K is the hardening coefficient of the material (K is taken as 1500), is the nanotwin content, n is the hardening index of the material (taken as 0.5), and ε is the true strain
[0027] Substituting the experimental data and related parameters, the relationship between the tensile strength of the alloy and the nanotwin content is obtained as follows:
[0028]
[0029] When the cold rolling reduction is 15%-30%, the content of the formed nano twins is 7.3%-32.8%, and the tensile strength of the alloy is 372-585 MPa.
[0030] In terms of electrical conductivity, according to the Hollomon model, the influence of nanotwin content on the electrical conductivity of the alloy is as follows:
[0031]
[0032] Among them, κ is the conductivity of the alloy after cold rolling, κ0 is the initial conductivity of the alloy (κ0 = 8.6% IACS), A is the strengthening coefficient of the material (A is taken as 1.05), is the nanotwin content, n is the hardening index of the material (generally taken as 0.5), and ε is the true strain
[0033] Substituting the experimental data and related parameters, the relationship between the electrical conductivity of the alloy and the content of nanotwins is obtained as follows:
[0034]
[0035] When the cold rolling reduction is 15%-30%, the content of the formed nano twins is 7.3%-32.8%, and the electrical conductivity of the alloy is 11.8%-27.5% IACS.
[0036] Beneficial Effects of the Invention
[0037] The present invention is based on the mechanism that low-temperature cold plastic deformation treatment promotes the nucleation and growth of nano twins. The AuNiCu alloy prepared by cold rolling treatment in a low-temperature environment of liquid nitrogen has the characteristics of high strength and high conductivity, and can meet the application requirements in technical fields such as precious metal-based electrical contacts. The obtained high-strength and high-conductivity AuNiCu alloy has a tensile strength of 372-585MPa and a conductivity of 11.8%-27.5%IACS. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0039] Example 1
[0040] In this embodiment, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy material is prepared by the following method.
[0041] (1) The alloy raw materials are placed in a vacuum tube furnace for smelting and the temperature is controlled at 1200°C.
[0042] (2) The obtained alloy is cast into AuNiCu alloy sheet through casting and cooling process.
[0043] (3) The obtained alloy sheet was placed in a tubular furnace for annealing, heated to 600°C and kept at this temperature for 1 hour, and then naturally cooled to room temperature.
[0044] (4) Clean the surface of the alloy sheet with anhydrous ethanol and dry it in a vacuum drying oven.
[0045] (5) The dried alloy sheet is immersed in liquid nitrogen for 1 hour to cool the alloy sheet to -196°C.
[0046] (6) The alloy sheet is quickly taken out of the liquid nitrogen and placed in a rolling mill for cold rolling with a reduction of 15% at a low temperature of -196°C. After each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling to ensure that it is always in a low temperature state of -196°C.
[0047] (7) After the alloy sheet is treated by liquid nitrogen low-temperature cold rolling, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy is obtained, whose tensile strength is 372 MPa and the conductivity is 11.8% IACS.
[0048] Example 2
[0049] In this embodiment, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy material is prepared by the following method.
[0050] (1) The alloy raw materials are placed in a vacuum tube furnace for smelting and the temperature is controlled at 1200°C.
[0051] (2) The obtained alloy is cast into AuNiCu alloy sheet through casting and cooling process.
[0052] (3) The obtained alloy sheet was placed in a tubular furnace for annealing, heated to 600°C and kept at this temperature for 1 hour, and then naturally cooled to room temperature.
[0053] (4) Clean the surface of the alloy sheet with anhydrous ethanol and dry it in a vacuum drying oven.
[0054] (5) The dried alloy sheet is immersed in liquid nitrogen for 1 hour to cool the alloy sheet to -196°C.
[0055] (6) The alloy sheet is quickly taken out of the liquid nitrogen and placed in a rolling mill for cold rolling with a reduction of 20% at a low temperature of -196°C. After each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling to ensure that it is always in a low temperature state of -196°C.
[0056] (7) After the alloy sheet is treated by liquid nitrogen low-temperature cold rolling, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy is obtained, whose tensile strength is 443 MPa and the conductivity is 17.2% IACS.
[0057] Example 3
[0058] In this embodiment, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy material is prepared by the following method.
[0059] (1) The alloy raw materials are placed in a vacuum tube furnace for smelting and the temperature is controlled at 1200°C.
[0060] (2) The obtained alloy is cast into AuNiCu alloy sheet through casting and cooling process.
[0061] (3) The obtained alloy sheet was placed in a tubular furnace for annealing, heated to 600°C and kept at this temperature for 1 hour, and then naturally cooled to room temperature.
[0062] (4) Clean the surface of the alloy sheet with anhydrous ethanol and dry it in a vacuum drying oven.
[0063] (5) The dried alloy sheet is immersed in liquid nitrogen for 1 hour to cool the alloy sheet to -196°C.
[0064] (6) The alloy sheet is quickly taken out of the liquid nitrogen and placed in a rolling mill for cold rolling at a low temperature of -196°C with a reduction of 25%. After each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling to ensure that it is always in a low temperature state of -196°C.
[0065] (7) After the alloy sheet is treated by liquid nitrogen low-temperature cold rolling, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy is obtained, whose tensile strength is 502 MPa and the conductivity is 22.3% IACS.
[0066] Example 4
[0067] In this embodiment, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy material is prepared by the following method.
[0068] (1) The alloy raw materials are placed in a vacuum tube furnace for smelting and the temperature is controlled at 1200°C.
[0069] (2) The obtained alloy is cast into AuNiCu alloy sheet through casting and cooling process.
[0070] (3) The obtained alloy sheet was placed in a tubular furnace for annealing, heated to 600°C and kept at this temperature for 1 hour, and then naturally cooled to room temperature.
[0071] (4) Clean the surface of the alloy sheet with anhydrous ethanol and dry it in a vacuum drying oven.
[0072] (5) The dried alloy sheet is immersed in liquid nitrogen for 1 hour to cool the alloy sheet to -196°C.
[0073] (6) The alloy sheet is quickly taken out of the liquid nitrogen and placed in a rolling mill for cold rolling at a low temperature of -196°C with a reduction of 30%. After each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling to ensure that it is always in a low temperature state of -196°C.
[0074] (7) After the alloy sheet is treated by liquid nitrogen low-temperature cold rolling, a nano-twin reinforced high-strength and high-conductivity AuNiCu alloy is obtained, whose tensile strength is 585 MPa and the conductivity is 27.5% IACS.
Claims
1. A high-strength and high-conductivity AuNiCu alloy and a preparation method thereof, characterized in that: The AuNiCu alloy material is subjected to liquid nitrogen low-temperature cold rolling treatment to form nano-twins with a lamellar structure, wherein the volume content of the nano-twins is between 7.3% and 32.8%. The obtained AuNiCu alloy has a tensile strength of 372-585 MPa and a conductivity of 11.8%-27.5% IACS.
2. The method for preparing the high-strength and high-conductivity AuNiCu alloy according to claim 1, characterized in that: The AuNiCu alloy sheet obtained by pretreatment is first immersed in liquid nitrogen to be cooled to the liquid nitrogen temperature, and then the alloy sheet is quickly taken out from the liquid nitrogen and put into a rolling mill, and the AuNiCu alloy is cold-rolled with a reduction of 15%-30% in a low temperature environment of liquid nitrogen; after each cold rolling, the alloy sheet is immediately immersed in liquid nitrogen for cooling.
3. The method for preparing the high-strength and high-conductivity AuNiCu alloy according to claim 2, characterized in that: In AuNiCu alloy, Au: 91%, Ni: 7.5%, Cu: 1.5%.
4. The method for preparing the high-strength and high-conductivity AuNiCu alloy according to claim 2, characterized in that: The pretreatment process of AuNiCu alloy sheet is as follows: (1) Melting: placing the alloy raw material in a vacuum tube furnace for melting at a melting temperature of 1050-1250° C.; (2) Casting: Casting the obtained alloy into AuNiCu alloy sheet through casting and cooling process; (3) Annealing: The obtained alloy sheet is placed in a tube furnace and heated to 500-700°C, kept at this temperature for 1-2 hours, and then naturally cooled to room temperature; (4) Cleaning and drying: Use anhydrous ethanol to clean the surface of the alloy sheet and place it in a vacuum drying oven to dry.